Enhancing Ecotourism Experiences in Forest Recreation Areas: Insights from Sukamantri Campground, Indonesia - Maura Aurelia; Tun Susdiyanti; Abdul Rahman Rusli; Dwi Agus Sasongko; Nia Yuliani (Forest and Nature, 2025)
Forest-based ecotourism plays a crucial role in balancing biodiversity conservation and sustainable community development. However, the success of ecotourism management relies heavily on understanding visitor satisfaction. This study applies the 4A framework (Attractions, Accessibility, Amenities, and Ancillary) to quantify visitor satisfaction at the Sukamantri Campground, located within Mount Halimun Salak National Park, Indonesia. A total of 67 respondents were selected using a purposive sampling method, and data were collected through structured interviews and questionnaires. Visitor satisfaction levels were assessed using a Likert-scale evaluation and analyzed quantitatively. The results reveal that Sukamantri Campground generally meets the 4A criteria, with high satisfaction scores for attractions (3.29), accessibility (3.20), and ancillary services (3.23), while amenities (2.80) were identified as the weakest aspect requiring improvement. The overall satisfaction index was 3.13, categorizing visitors as “satisfied.” Despite relatively positive perceptions, facilities (particularly toilets and supporting infrastructure) remain critical factors influencing visitor experience. This study highlights the importance of integrating the 4A framework into forest recreation management to enhance visitor experiences while maintaining environmental sustainability. The findings provide valuable insights for ecotourism managers and policymakers to develop targeted strategies, including upgrading facilities, improving digital promotion, and strengthening collaboration with local communities to achieve sustainable forest-based tourism.